The Genome Sequence DataBase version 1.0 (GSDB): from low pass sequences to complete genomes. - Harger, C (1997)
The Genome Sequence DataBase (GSDB) has completed its conversion to an improved relational database. The new database, GSDB 1.0, is fully operational and publicly available. Data contributions, including both original sequence submissions and community annotation, are being accomplished through the use of a graphical client-server interface tool, the GSDB Annotator, and via GIO (GSDB Input/Output) files. Data retrieval services are being provided through a new Web Query Tool and direct SQL. All methods of data contribution and data retrieval fully support the new data types that have been incorporated into GSDB, including discontiguous sequences, multiple sequence alignments, and community annotation.